DAMPAK GAME ONLINE MOBILE LEGEND TERHADAP KESEHATAN MENTAL REMAJA : Studi Kasus di Desa Munjul Blok Kedung Subur Kec. Astanajapura Kab. Cirebon (Prodi Tasawuf dan Psikoterapi, Fakultas Agama Islam, Universitas Muhammadiyah Cirebon, 2022)
This research examines the impact of the online game Mobile Legend on the mental health of its players. This, once again, proves that technological products in excess will have an impact on a person's psychological development. This research was conducted in Munjul Village, Kedung Subur Block, Astanajapura District, Cirebon, West Java. The purpose of this study is to determine the extent to which the Mobile Legend online game has an impact on the mental health of adolescents in the village we studied. In addition, this research is also to analyze the influence of adolescents who are addicted to online games based on the perspective of psychology and Islamic teachings. This research used a qualitative method with description-analytical approach. Some of the findings we obtained include: teenagers who are addicted to Mobile Legend online games experience feelings of anxiety; spiritual worship does not seem to be sincere in its implementation.